2021
DOI: 10.3727/096504021x16130322409507
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting PLK1 by ON-01910.Na Is Effective in Local Treatment of Retinoblastoma

Abstract: Cell cycle deregulation is involved in pathogenesis of many cancers, and often associated with protein kinase aberrations, including the polo-like kinase 1 (PLK1). Wehereby used retinoblastoma, an intraocular malignancy that lacks targeted therapy, as a disease model and set out to reveal targetability of PLK1 with a small molecularinhibitor ON-01910.Na. First, transcriptomic analysis on patient retinoblastoma tissues suggested that cell cycle progression was deregulated and confirmed that PLK1pathway was upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…The 100 nm Rig concentration is consistent with Rig concentrations used in other studies; in fact, in all these works, Rig exhibited the same efficacy in reducing the viability of the cell lines evaluated, with effective concentrations starting approximately at 50–100 nM [ 6 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The 100 nm Rig concentration is consistent with Rig concentrations used in other studies; in fact, in all these works, Rig exhibited the same efficacy in reducing the viability of the cell lines evaluated, with effective concentrations starting approximately at 50–100 nM [ 6 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Resultssupporting
confidence: 86%
“…Moreover, Rig is capable of inducing senescence or cell death by apoptosis in several tumor cell lines, both in vitro and in vivo [ 4 , 6 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], increasing the production of ROS and altering the expression of numerous proteins involved in apoptosis (p53, BAX, MDM2) and in the formation of metastases (E-cadherins, matrix metalloproteinases 2 and 9) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rig is a multi-kinase inhibitor that could be considered an alternative therapeutic option for different solid tumors and hematologic malignancies. Its efficacy against myelodysplastic syndrome, head and neck cancer, hepatocellular carcinoma, retinoblastoma, and glioblastoma has already been demonstrated [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Moreover, on the website (July 2021) it is possible to highlight that Rigosertib is involved in various clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…As is the case with other RB1-deficient cancer cells, primary RB tumors display high expression levels of several mitotic genes, including AURKB, polo-like kinase 1 (PLK1), mitotic arrest deficient 2 like 1 and BUB1 mitotic checkpoint serine/threonine kinase (43,44,89,90). Two recent studies have demonstrated that pharmacological inhibition of AURKB and PLK1 in RB cells resulted in cell cycle arrest and increased apoptosis, whereas the effects of the inhibitors on a nontumoral retinal pigment epithelial cell line (ARPE-19) were negligible under identical conditions, which was indicative of a higher sensitivity of RB cells to these inhibitors (89,91). Although both studies have not examined whether inhibition of these upregulated mitotic kinases causes chromosomal aberrations that may eventually lead to cell death, the results support the possibility that cancer cells with hyperactive mitotic checkpoint signaling due to RB1 loss might depend on AURKB and PLK1 for efficient mitotic exit and survival, establishing a synthetic lethal relationship with RB1 deficiency upon their inhibition.…”
Section: Genome Maintenance Mechanisms In Rbmentioning
confidence: 99%